2004
DOI: 10.1038/sj.hdy.6800516
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for paternal inheritance of mitochondrial DNA in the sheep (Ovis aries)

Abstract: The mitochondrial DNA of 172 sheep from 48 families were typed by using PCR-RFLP, direct amplification of the repeated sequence domain and sequencing analysis. The mitochondrial DNA from three lambs in two half-sib families were found to show paternal inheritance. Our findings provide direct evidence of paternal inheritance of mitochondria DNA in sheep. A total of 12 highly polymorphic microsatellite markers, which mapped on different chromosomes, were employed to type the sheep population to confirm family re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 22 publications
0
47
0
2
Order By: Relevance
“…4A-D), opinions may vary as to whether the same holds true for sperm mtDNA. Some population studies defend the possibility of paternal-maternal mtDNA recombination after sperm mtDNA leakage (Awadalla et al, 1999;Eyre-Walker et al, 1999;Hagelberg, 1999a;Zhao et al, 2001) and it is yet to be demonstrated that the degradation of sperm mitochondrial proteins is parallel to the hydrolysis of sperm mtDNA. It should be considered that the sperm mitochondria can survive inside other cells (Manfredi et al, 1997).…”
Section: Evolutionary Considerationsmentioning
confidence: 98%
“…4A-D), opinions may vary as to whether the same holds true for sperm mtDNA. Some population studies defend the possibility of paternal-maternal mtDNA recombination after sperm mtDNA leakage (Awadalla et al, 1999;Eyre-Walker et al, 1999;Hagelberg, 1999a;Zhao et al, 2001) and it is yet to be demonstrated that the degradation of sperm mitochondrial proteins is parallel to the hydrolysis of sperm mtDNA. It should be considered that the sperm mitochondria can survive inside other cells (Manfredi et al, 1997).…”
Section: Evolutionary Considerationsmentioning
confidence: 98%
“…However, it was recently shown in a patient with mitochondrial myopathy that the pathogenic mtDNA was of paternal origin (Schwartz and Vissing, 2002). Evidence for the occasional paternal transmission of mtDNA has also been reported in sheep, mice, cattle, mussels, and insects (Zhao et al, 2004). Although rare, the paternal inheritance of mtDNA may have a significant impact on evolution and on disease development.…”
Section: Mitochondrial Dna Inheritancementioning
confidence: 99%
“…Organisms such as the blue mussel (Cogswell et al, 2006) and Chlamydomonas (Aoyama et al, 2006) inherit paternal mitochondria but most mammals inherit mitochondria and mtDNA maternally (Kuroiwa, 1991;Birky, 1995), with paternal mitochondrial inheritance being a rare event, as proposed in sheep (Zhao et al, 2004). Early theories attempted to explain maternal mtDNA inheritance by the dilution of paternal mtDNA in the oocyte (Hecht et al, 1984;Jansen and de Boer, 1998;Birky, 2001;Diez-Sanchez et al, 2003).…”
mentioning
confidence: 95%